2012
DOI: 10.1007/s10815-012-9923-7
|View full text |Cite
|
Sign up to set email alerts
|

A highly sensitive electrochemiluminescence immunoassay for detecting human embryonic human chorionic gonadotropin in spent embryo culture media during IVF-ET cycle

Abstract: Purpose To investigate the stability and repeatability of electrochemiluminescence immunoassay (ECLIA) for betahCG detection in embryo spent culture media. To evaluate the correlation between the viability of preimplantation embryo and beta-hCG profile by the new assay. Methods In a retrospective study, a total of 357 spent culture media from day1 to day5 were individually collected and quantified by ECLIA. The blank controls and reliability test were performed with normal saline/pure culture media. Results 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…[ 11 12 ] HCG is a heterodimeric placental glycoprotein hormone that is required to maintain pregnancy and is initially produced by the blastocyst 6–8 days after fertilization. [ 13 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 12 ] HCG is a heterodimeric placental glycoprotein hormone that is required to maintain pregnancy and is initially produced by the blastocyst 6–8 days after fertilization. [ 13 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms have been used to design clinical studies to assess clinical outcomes upon implantation. Xiao-Yan et al measured human embryonic human chorionic gonadotropin in embryo culture media that was used during in vitro fertilisation (IVF) cycles, and they found a positive correlation between the beta-hCG concentration and the implantation rate, which indicates that the hCG that is secreted by embryos could be used as a biomarker for embryo selection in IVF cycles [ 13 ]. Mansour et al reported the first time use of an intrauterine injection of hCG before the embryo transfers, and they found a significant improvement in the pregnancy rates of the IVF cycles [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly Xiao-Yan et al found that there was a significantly higher β-HCG concentration in the spent culture medium of embryos resulting in pregnancy compared to those that did not. This significant difference was present in day 3 embryos (P= 0.041) but was more pronounced at the blastocyst (day 5) stage (0.004) [10] . The results of this study are totally in line with these earlier findings.…”
Section: Discussionmentioning
confidence: 84%